2015
DOI: 10.3390/su7079444
|View full text |Cite
|
Sign up to set email alerts
|

Built Environmental Designs in Promoting Pedestrian Safety

Abstract: This study examined two-level (road environments and census tracts) built environments related to the probability of severe injury for pedestrians. In total, 1407 pedestrian-vehicle crashes (years 2008-2012) were identified from 140 census tracts in the city of Austin. Two multilevel models were applied to examine pedestrian injury severity by using level-1 factors (individual characteristics, road environments, and area characteristics around the crash location) and level-2 factors (characteristics of census… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
36
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 42 publications
10
36
1
1
Order By: Relevance
“…Research on the severity of pedestrian-vehicle crashes has been ongoing for many years in multiple countries [1][2][3][8][9][10]13,14,[16][17][18][19][20][21][22][23]. Many studies have identified factors that affect the severity of pedestrian injuries, including the personal characteristics of pedestrians and drivers, temporal characteristics, and aspects of the built environment, such as road characteristics and land use.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on the severity of pedestrian-vehicle crashes has been ongoing for many years in multiple countries [1][2][3][8][9][10]13,14,[16][17][18][19][20][21][22][23]. Many studies have identified factors that affect the severity of pedestrian injuries, including the personal characteristics of pedestrians and drivers, temporal characteristics, and aspects of the built environment, such as road characteristics and land use.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Walking is the most basic means of transportation [1,2]. Its importance for improving public health, saving energy, and reducing traffic congestion and air pollution has long been acknowledged.…”
Section: Introductionmentioning
confidence: 99%
“…Hal ini mengakibatkan resiko kendaraan bermotor bertabrakan dengan pejalan kaki meningkat seiring bertambahnya jumlah kendaraan bermotor yang berinteraksi dengan pejalan kaki (Maghfur, 2015). Jika lingkungan tidak dapat menjamin keamanan pejalan kaki, maka upaya untuk meningkatkan kegiatan berjalan kaki dapat mengancam keselamatan pejalan kaki dan meningkatkan kematian dan cedera bagi pejalan kaki (Yu, 2015).…”
Section: Keindahanunclassified
“…The results showed that when locating sites for work premises that are walkable and when also applying some policies at the same areas, then the employees become influenced to actively commute to their work more often. Also, Yu (2015) examined pedestrian injury severity indicating that individual characteristics, road environments and area characteristics around the crash location affect the pedestrian injury positively. Further, ZunigaTeran et al (2017) suggested a "Walkability Framework" to be used as a model to measure interactions between built environment and physical activity.…”
Section: Socio-economical and Environmental Factors Affecting Active mentioning
confidence: 99%